Economic Empowerment of Scheduled Tribe Women through Panchayati Raj Initiatives (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2025)
Economic empowerment of women is a cornerstone of inclusive development and social justice. In India, Scheduled Tribe (ST) women face double marginalization—both as women and as members of disadvantaged communities. The 73rd Constitutional Amendment (1992), by institutionalizing Panchayati Raj Institutions (PRIs) and reserving seats for women, provided a critical pathway for their participation in governance. This article examines the impact of Panchayati Raj initiatives on the economic empowerment of ST women. It highlights their involvement in decision-making, access to development schemes, role in self-help groups, livelihood generation, and policy implementation. The study also explores challenges and suggests future directions.